2022
DOI: 10.3390/ijerph19137870
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness of Chinese Primary School Students across the Coronavirus (COVID-19) Outbreak: A Retrospective Repeated Cross-Sectional Study

Abstract: Social distancing measures against COVID-19 imposed restrictions on students that may have affected their physical health and fitness. The objective of this study was to investigate the change in physical fitness of primary school students across the coronavirus outbreaks from 2019 to 2021. This was a retrospective repeated cross-sectional study. We obtained the annual physical and fitness assessment data measured every November for all students at the same primary school in Guangzhou, China. There was a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Level of flexibility was assessed using a sit-and-reach test. The curve was measured in cm by bending the upper body based on the baseline, which left a forward curve measured in a seated state [ 15 ]. Obesity status was determined based on body mass index, which was calculated using each participant’s height and weight [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Level of flexibility was assessed using a sit-and-reach test. The curve was measured in cm by bending the upper body based on the baseline, which left a forward curve measured in a seated state [ 15 ]. Obesity status was determined based on body mass index, which was calculated using each participant’s height and weight [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, a study on physical fitness changes in the midst of the COVID-19 situation was conducted on students in Japan, China, and Austria. Most students reported that their physical fitness levels were decreasing [ 15 , 16 , 17 , 18 ]. Moreover, various studies have examined educational, in addition to physical, aspects that have changed because of the COVID-19 situation.…”
Section: Introductionmentioning
confidence: 99%
“…The professional development path for health communication practice should encompass areas such as sports health knowledge, sports injury prevention, sports rehabilitation, physical training, and fun fitness training ( 12 ). Additionally, physical education teachers need to recognize that the audience for health communication extends beyond just students in school ( 53 ). Therefore, the professional development path for health communication practice also emphasizes the active understanding of different target groups and acknowledging their specific needs in health promotion.…”
Section: Discussionmentioning
confidence: 99%